P017 Am I sleepy? – Subjective Sleepiness and Drowsy Driving: A systematic review and meta-analysis. (7th October 2021) - Cai, A; Manousakis, J; Lo, T; Horne, J; Howard, M; Anderson, C
Abstract: Introduction: Driving impairment due to sleep loss is a major contributor to motor vehicle crashes resulting in severe injury or fatalities. Ideally, drivers should be aware of their sleepiness and cease driving to reduce risk of a crash. However, there is little consensus on how accurately drivers can identify sleepiness, and how this relates to subsequent driving impairment. To examine whether drivers are aware of their sleepiness, we systematically reviewed the literature. Methods: The research question for this review was "are drivers aware of sleepiness while driving, and to what extent does subjective sleepiness accurately reflect driving impairment?". Our search strategy led to thirty-four simulated/naturalistic driving studies for review. We then extracted the relevant data. Correlational data were examined using meta-analysis, while predictive data were assessed via narrative review. Results: Results showed that drivers were aware of sleepiness, and this was associated with both driving impairment and physiological drowsiness. Overall, subjective sleepiness was more strongly correlated (a) with ocular and EEG-based outcomes (rweighted = .70 and .73, respectively, p<.001), rather than lane position and speed outcomes (rweighted = .46 and .49, respectively, p<.001); (b) under simulated driving conditions compared to naturalistic drives; and (c) when the Karolinska Sleepiness Scale was used to measure subjective sleepiness. Lastly, high levels of sleepiness significantly predicted crash events and lane deviations. Discussion: This review presents evidence that drivers are aware of sleepiness when driving, and suggests that interventions such as stopping driving when feeling 'sleepy' may significantly reduce crash risk.